1. CARL SCHMITT BETWEEN HISTORY AND MYTH. Issue 3 (5th September 2017) - FINCHELSTEIN, FEDERICO
ABSTRACT: Carl Schmitt's work defines the history and theory of political myth. But analyzing it represents a challenge to historians and theorists alike. For many historians, Schmitt should be analyzed in his own context, whereas theorists study his writings without enough consideration of the specific context in which he conceived his texts. In this essay, I argue that Schmitt not only contributed to the fascist glorification of the mythical and its novel enactment as the driving force of fascism, but he also represents one of the most intriguing and influential interpreters of the political theory of myth, challenging in turn theories of democracy and the role of reason and secularism in historiography.